2014
DOI: 10.1007/s12594-014-0154-7
|View full text |Cite
|
Sign up to set email alerts
|

Regional Appraisal of the Fluoride Occurrence in Groundwaters of Andhra Pradesh

Abstract: Fluoride (F−) is essential for normal bone growth, but higher concentration in the drinking water causes health problems which are reported in many states of India. Andhra Pradesh is one of the states which suffer from excess fluoride in groundwater particularly in the hard rock terrain. In this context, a study was conducted in Andhra Pradesh based on chemical analysis of water samples from hydrograph net work stations (dug wells) and exploratory bore wells. The concentration of fluoride in groundwaters range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The F − content was from 0.26 to 2.30 (with an average of 0.99) mg/L in the present study area. The country rocks, containing the F − bearing minerals (apatite, biotite and hornblende), and the occurrence of clays are the main responsible for the F − content in the present study area, as also suggested by Rao et al (2014) and Subba Rao et al (2017b). The extensive use of phosphate fertilizers for higher crop yields is the secondary source for enrichment of F − in the groundwater (Subba Rao 2017b).…”
Section: Groundwater Quality and Chemistrysupporting
confidence: 54%
“…The F − content was from 0.26 to 2.30 (with an average of 0.99) mg/L in the present study area. The country rocks, containing the F − bearing minerals (apatite, biotite and hornblende), and the occurrence of clays are the main responsible for the F − content in the present study area, as also suggested by Rao et al (2014) and Subba Rao et al (2017b). The extensive use of phosphate fertilizers for higher crop yields is the secondary source for enrichment of F − in the groundwater (Subba Rao 2017b).…”
Section: Groundwater Quality and Chemistrysupporting
confidence: 54%
“…indicates its lower geochemical mobility and its absorption on clays (Hem 1991;Drever 1997). Fluoride minerals, agro-chemicals, etc., are the sources of F -in the groundwater (Ayoob and Gupta 2006;Ahmed 2014;Rao et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…indicates its lower geochemical mobility and its absorption on clays (Hem 1991;Drever 1997). Fluoride minerals, agro-chemicals, etc., are the sources of Fin the groundwater (Ayoob and Gupta 2006;Rao et al 2014).…”
Section: Resultsmentioning
confidence: 99%